EFEKTIVITAS PEMBELAJARAN AL-QUR’AN HADIS MATERI “KANDUNGAN QS. ASH-SYAMS TENTANG KEKUASAAN ALLAH SWT ” DENGAN METODE DISCOVERY LEARNING DI MTSN 2 KOTA BIMA - Suryati Suryati (Fitrah, 2022)
This research is a descriptive qualitative research that aims to describe the Effectiveness of Learning the Qur'an and Hadith in the Material "Power and Mercy of Allah Swt" Using the Discovery Learning Method at MTSN 2 Kota Bima in the 2022/2023 academic year. This research is motivated by the learning difficulties experienced by students in terms of memorizing and translating QS. Ash-Shams verses 1-10. From this study, it was found that the speed of understanding of students increased by using the discovery learning method. The absorption of these students is marked by the ability of students to explain the contents of the QS. Ash-Shams verses 1-10.